"But, I mean, the thing has become a myth that nobody can live up to." Lou Reed’s narrative of transgression, stigma, self and resistance - Müller, Thaddeus (Deviant behavior, 2023)
This study contributes to the criminological transgression literature with an in-depth ethnographic analysis of Reed’s narrative of transgression, stigma, self and resistance. This analysis includes two intertwined perspectives on rule breaking, 1) the transgression concept within cultural criminology and 2) deviance studies with its focus on labeling and stigma. This combination creates an academic focus that includes the empowering and disempowering qualities of rule breaking. Lou Reed’s rich narrative extending over a period of six decades shows that the meaning making process of his transgressions was shaped by Reed’s interactions within several transgressive social worlds, the commodified mediatized representations of his work, and societal transformations changing the meaning of drugs and sexualities. In addition, this article shows that Reed’s transgressions were intimately related to stigma and shame, an angle which is hardly explored within cultural criminology and deserves more attention in order to further our understanding of the social meanings of transgression.